Do bank insiders impede equity issuances? - Martin Goetz; Luc Laeven; Ross Levine (European Central Bank (ECB), 2021)
We evaluate the role of insider ownership in shaping banks' equity issuances in response to the global financial crisis. We construct a unique dataset on the ownership structure of U.S. banks and their equity issuances and discover that greater insider ownership leads to less equity issuances. Several tests are consistent with the view that bank insiders are reluctant to reduce their private benefits of control by diluting their ownership through equity issuances. Given the connection between bank equity and lending, the results stress that ownership structure can shape the resilience of banks-and hence the entire economy-to aggregate shocks.
Keywords: G32; G21; G28; 330; Ownership Structure; Equity Issuances; Banking; Financial Crisis; Regulation